Qur’anic Foundations for Time Management in Alhikam Aleatayiya (The International Journal for Scientific Research, 2024)
The Holy Qur’an represents the intellectual reference and the basic starting point for all sciences and knowledge, as it represents the axis around which all legal sciences revolve. With the passage of time, scholars expanded in deducing Quranic knowledge in a way that keeps pace with different eras. This paper deals with the effort of one of the distinguished scholars who belong to the doctrine of Islamic Sufism, which is the science of He is concerned with purification and linking life in all its details to God Almighty. This is the divine scholar Ibn Ata Allah of Alexandria. The paper discusses the issue of time management in Alhikam Alatayia and its Qur’anic foundations.It has become clear that Ibn Ata Allah presented a special vision on this subject based on Qur’anic verses, and this is what this paper reveals, which came in an introduction and three sections. The first topic dealt with the introduction of Ibn Ata Allah and his wisdom, and the second topic dealt with the definition of time in Sufi thought, and the topic was the third is a survey of the rulings related to time and their Qur’anic meanings.
Keywords: Alhikam Alatayia; Foundations; the Qur’an; Sufism; Time Management